2018
DOI: 10.1002/sdtp.12463
|View full text |Cite
|
Sign up to set email alerts
|

P‐203: Late‐News Poster: Novel Techniques for Highly Stable Luminescent Perovskite Halide Quantum Dots

Abstract: Perovskite quantum dots (QDs) are promising materials for display application due to their high optical properties, such as: high PLQY, narrow FWHM and tunable emission wavelengths. The present work shows the further progress in enhancement of perovskite QDs stability, resistance to photodegradation and PL quenching at high temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…S8. The gradual increase in the PL intensity in the first 3 h could be attributed to the evaporation of reduced solvents and the formation of additional emissive centres linked to the dynamics of CsPbBr 3 perovskite NCs 33,34 . In the subsequent 12 h, the PL intensity remained stable under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8. The gradual increase in the PL intensity in the first 3 h could be attributed to the evaporation of reduced solvents and the formation of additional emissive centres linked to the dynamics of CsPbBr 3 perovskite NCs 33,34 . In the subsequent 12 h, the PL intensity remained stable under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The photostability exceeds that of other untreated CsPbBr 3 perovskite NCs, which degrade within a few hours 3538 . The reduction of the PL intensity after 16 h of intense continuous irradiation under a focused UVC light source is most likely due to the thermal degradation and photooxidation of lead atoms 33,39,40 . Further improvement of the photostability of the CsPbBr 3 film is undoubtedly possible by employing a core/shell structure 38 , surface passivating ligands 24,33 and encapsulation 35 , as demonstrated in other prior works.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the QDs configuration is important to assess their stability, as the QD composition and interaction between the atoms are determining factors for the QD optical properties and stability [27]. Numerous researchers reported that inorganic PQDs exhibit superior properties for optical display compared to other types of PQDs in terms of low PL quenching and PL peak shifting at elevated temperature, as shown by Sinatra et al [27,28]. While PQDs have excellent optical properties, their display applications are limited to green emitting CsPbBr 3 PQDs.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2a, the FAPbBr 3 @PVDF composite film exhibited brilliant green photoluminescence with a distinct peak centered at 531 nm, corresponding to the band-edge exciton emission from the embedded FAPbBr 3 nanocrystals. [12][13] The photoluminescence quantum yield (PLQY) reached over 93%, and full width at half maximum (FWHM) of the emission spectra remained around 23 nm. The narrow band emission ensures the possibility of realistic color rendering.…”
Section: Characterizations Of the Fapbbr3@pvdf Composite Filmmentioning
confidence: 99%